The role of primary health care collaborative care models in mental health management: a narrative review - Shukla, Pranav Sanjay; Zia, Shahab Ud Din; Mun, Sojeong; Van de Vel, Gilles; Chalasani, Roopa; Khan, Safeera (International Journal of Research in Medical Sciences, 2025)
Collaborative care models (CCMs), which embed behavioral-health screening, care management, and psychiatric consultation in routine primary-care workflows, consistently outperform usual care. A narrative synthesis of randomized trials, systematic reviews, implementation studies, and policy documents published from January 2010 to April 2024 shows that CCMs reduce depression and anxiety symptoms, boost remission and adherence, and raise patient satisfaction. Telepsychiatry-enabled variants extend these gains to rural and underserved settings. Economic analyses reveal lower total costs driven by fewer hospitalizations and emergency visits. Persistent barriers, fragmented reimbursement, incompatible IT systems, workforce shortages, and stigma limit scale-up. Targeted policy reforms, integrated health-IT, and expanded training are therefore essential to realize CCMs’ full potential in primary care.